The CABANA model 2017–2022: research and training synergy to facilitate bioinformatics applications in Latin America - Campos-Sánchez, Rebeca; Willis, Ian; Gopalasingam, Piraveen; López-Juárez, Daniel; Cristancho, Marco; Brooksbank, Cath; , on behalf of The CABANA Consortium (Frontiers in Education, 2024)
The CABANA project (Capacity Building for Bioinformatics in Latin America) was funded by the UK's Global Challenges Research Fund in 2017 with the aim to strengthen the bioinformatics capacity and extend its applications in Latin America focused on three challenge areascommunicable diseases, sustainable food production and protection of biodiversity. For five years, the project executed activities including data analysis workshops, train-the-trainer workshops, secondments, eLearning development, knowledge exchange meetings, and research projects in ten countries. The project was successful in accomplishing all its goals with a major impact on the region. It became a model by which the research needs determined the training that was delivered. Multiple publications and over 800 trainees are part of the legacy of the project.